Neonatal orally administered curcumin: impact on the metabolic response and renal histology of Sprague-Dawley rats fed a high-fructose diet until adolescence - Ibrahim, Kasimu Ghandi (2023)
Effect of curcumin and fructose on body mass The male and female rats gained significant body mass (P < 0.0001), from induction through weaning and termination (Table 1). However, there was no significant difference (p > 0.05) across the treatment groups at the different time points in both sexes.